4-[(E)-(3-Methyl-5-thioxo-4,5-dihydro-1H-1,2,4-triazol-4-yl)iminomethyl]benzonitrile - Zhao, Yu-Yuan (International Union of Crystallography, 2008)
In the title compound, C(11)H(9)N(5)S, the dihedral angle between the mean planes of the thione-substituted triazole ring and benzonitrile ring is 4.28 (3)°. Intermolecular N—H⋯S hydrogen bonds link the molecules together into characteristic dimers.